The Effectiveness of the Solution Focused Brief Group Counseling Guidebook in Reducing Fear of Missing Out (FOMO) in Students - Ikrimania Mosleh; Bakhruddin All Habsy; Denok Setiawati (Bisma The Journal of Counseling, 2026)
This study aims to develop a Solution Focused Brief group counseling guidebook that meets the criteria of acceptability, which consists of four aspects, namely: accuracy, usefulness, feasibility, and appropriateness, and to test its effectiveness in reducing FOMO in adolescents. The study uses the Borg and Gall research and development (R&D) model, which consists of seven stages. Research participants included expert validators, guidance counselors, and students. Data were collected through questionnaires using validity assessment instruments administered to experts and prospective users to assess the level of acceptability of the developed guidebook, as well as questionnaires using FOMO instruments administered to students. Data analysis was conducted by applying product validity methods and effectiveness tests through a comparison of pretest and posttest results. The effectiveness test results showed that the intervention using the FOMORE guide had a significant impact on reducing FOMO in adolescents. Thus, the Solution Focused Brief group counseling guidebook has been proven to be feasible for use in reducing FOMO in adolescents, and it is recommended for implementation by guidance counselors as an innovative intervention in responsive services at schools.